(untitled) (Research, Society and Development, 2023)
Introduction: The consumption of the psychostimulant Methylphenidate (Ritalin®), indicated as a treatment option for Attention Deficit Hyperactivity Disorder (ADHD), is a current public health challenge in many parts of the world. The consumption of this medicine gradually increases, as its non-therapeutic use grows among students who aim to enhance their studies. Administering it without professional guidance and without medical prescriptions. Objective: The purpose of this study was to describe the health risks of using Ritalin® without therapeutic indication. Proposed Methodology: A descriptive and exploratory study was carried out based on an integrative literature review, conducting research and collecting scientific data organized through the investigation of articles associated with the object of study. A table was prepared with the purpose of objectively presenting the main information collected. Results: The results obtained were that until 2009 there were no published studies on the “non-medical” use of Ritalin® in Brazil. However, this subject has currently been widely discussed in the field of medicine due to the ethical and moral obstacles and the risks to the health of users. Therefore, it is believed that the group of medical students is more likely to use this medication to “boost the brain”. Final Considerations: The data show that there is a high prevalence of methylphenidate use, mainly by medical students, both prescribed and non-prescribed, mainly aiming at academic performance, agreeing with the literature regarding the possibility of a relationship between the course and the use of this psychostimulant.